The clergy club - Crothers, John, 1951- (ATF Theology, 2018)
The Clergy Club, as the title suggests, looks at the disconnection that exists between the clergy and the laity in the Catholic Church, and the "club" mentality on the part of the Church hierarchy that underpins it. Many examples are cited that reveal an attitude among priests and bishops of elitism and aloofness, as well as the clergy's inability to see the world from the perspective of the laity, even with the best intentions. Many questions are asked, such as "Where does this 'club' attitude come from? How does it express itself? How is it reinforced by Church structures and theology? What was Jesus' approach to both clergy and laity? Why is Pope Francis so vehement in his criticism of clericalism? Some practical initiatives are also suggested as a way of bringing about change in the clerical culture, a change that would help to rid the Church of clericalism, and in the process bring the clergy and laity closer together.